Small becomes big, fast: Adolescent perceptions of how social media features escalate online conflict to offline violence. (March 2021) - Elsaesser, Caitlin; Patton, Desmond Upton; Weinstein, Emily; Santiago, Jacquelyn; Clarke, Ayesha; Eschmann, Rob
Highlights: Adolescents describe how social media features escalate online threats to violence. Focus groups participants (N = 41) were recruited from a violence prevention program. Online conflict over romantic relationships, especially for girls, lead to violence. Video streaming and comments on social media intensified online threats. Abstract: While youth violence is a longstanding public health problem, social media has changed how youth experience conflict. Qualitative work documents that threats are now being expressed online and escalate to offline violence, in a phenomenon termed internet banging. The goal of the present study was to examine adolescent perceptions of how social media features escalate online conflict to offline fights in a sample of adolescents living in disinvested neighborhoods in Hartford. To explore this topic, we foreground adolescent voices to document 1) what adolescents see as the sources of conflict online, and 2) how adolescents see social media features (e.g., photos, comments, livestream video) in escalating conflict online. We draw on Nesi et al.'s (2018a, 2018b) transformational framework and Phenomenality and Ecological Systems Theory (Spencer et al., 1995) to guide our understanding of the role of these features in this form of interpersonal peer conflict. Four focus groups with 41 American adolescents (ages 12 to 19, 73% self-identified as Black) solicited perspectives on violence resulting from social media conflict. Three coders analyzed data in Dedoose, guided by systematic textual coding using a multi-step thematic analysis. Major findings underscore that adolescents described romantic conflict as a significant source of social media fights that led to offline violence, particularly for conflict involving girls. Further, our findings underscore that adolescents engaged in social media threats often do not go online with the intention to fight. Rather, adolescents expressed keen awareness that social media intensifies interpersonal slights, and specifically identified video streaming and comments as social media features that intensify social media threats, increasing the likelihood of offline violence.